Bioinformatic tools in the study of ancient dogs: preliminary results of an Iberian case study - Blaschikoff, Ludmilla (2019)
In this study, we attempted to carry out a genomic amplification of ancient DNA from four pre-historic Iberian dogs using the Illumina sequencing method; to assign mtDNA sequences to the major dog haplogroups and to characterize some phenotypic traits of these dogs.